Understanding public perception of health examination services: Key factors influencing satisfaction in Türkiye - Kübranur Çebi Karaaslan; Hülya Diğer; Tubanur Çebi (PLoS ONE, 2025)
The aim of this study is to evaluate the level of satisfaction with health examination services in Türkiye. It is thought that the findings will contribute to the more effective management of the health service process and offer potential solutions to identified problems. Notably, a significant portion of the problems encountered in healthcare services tends to arise during the examination phase. Therefore, this research was conducted to address these problems by thoroughly analyzing public satisfaction, with the expectation that such an approach could provide actionable insights for resolving these problems. In the study, the micro data set of the 2023 Life Satisfaction Survey conducted by the Turkish Statistical Institute was used. The analysis process was carried out with a two-stage method. In the first stage, Pearson’s χ² test was used to evaluate whether the independent variables had a statistically significant relationship with satisfaction with health examination services. In the second stage, a considering the binary categorical structure of the dependent variable, a logit regression model was applied to estimate the relationship between satisfaction with health examination services and the independent variables. The findings revealed that 61.85% of Turkish citizens were satisfied with health examination services. Furthermore, this level of satisfaction was significantly affected by a wide range of sociodemographic, individual, and institution-related factors. The study’s findings suggest that aligning individuals’ demands in the health service process with guidance from field experts and developing targeted policies could lead to improved satisfaction with health examination services. In addition, it is foreseen that the concept of trust is important in the satisfaction that constitutes the main subject of the study in health services and in the negative situations experienced in different subjects. Based on these insights, initiatives can be taken to increase trust in the health system through health policies to be designed. Furthermore, the results highlight the growing importance of digitalization and digital hospitals in healthcare. Further progress in this direction will increase the satisfaction with health examination and contribute to positive results in health services.